Gender Equality in Educational Achievement : An East-West Comparison - Sylke Viola Schnepf (Institute for the Study of Labor (IZA), 2004)
Data on educational access show gender parity of pupils attending primary and secondary schools in transition countries. The first aim of this analysis is to examine whether the gender balance in educational access translates also into gender equality in educational achievement. There are several and very recent international surveys available measuring pupils learning achievement and functional literacy in schools. These surveys are typically analysed in isolation from each other even though they are very different in their design. The second aim of this paper is to evaluate whether we find a robust pattern on gender equality in achievement across different sources: the Trends in International Maths and Science Study (TIMSS), the Programme of International Student Assessment (PISA) and the Programme of International Reading Literacy Study (PIRLS). Besides a comparison of gender differences in mean achievement for transition and OECD countries we discuss alternatives for translating achievement scores into something easily understood. In addition, differences in boys? and girls? achievement distributions and determinants of gender inequality will be examined.
Keywords: J16; J24; I21; 330; education; gender inequality; Central and Eastern Europe; PISA; TIMSS; PIRLS; Bildungsniveau; Bildungschancen; Geschlechterdiskriminierung; Frauenbildung; Vergleich; OECD-Staaten; Osteuropa